2008
DOI: 10.1111/j.1365-3059.2008.01858.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of jasmonic acid signalling in bacterial wilt disease resistance induced by biocontrol agent Pythium oligandrum in tomato

Abstract: When the biocontrol agent Pythium oligandrum (PO) colonizes the rhizosphere, it suppresses bacterial wilt disease in tomato ( Solanum lycopersicum cv. Micro-Tom) caused by Ralstonia solanacearum , and a homogenate of its mycelia exhibits elicitor activity, inducing an ethylene (ET)-dependent defence response in Micro-Tom. Since salicylic acid (SA) and jasmonic acid (JA) play an important role in plant defence responses to pathogens, the involvement of SA-and JAdependent signal transduction pathways in resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 38 publications
2
50
1
6
Order By: Relevance
“…For instance, in tomato the JA-insensitive mutant def1 (defenseless 1) and the ET-insensitive mutant Nr (Never ripe) were not capable of mounting ISR against the oomycete pathogen Phytophthora infestans upon colonization of the roots by the PGPR Bacillus pumilus SE34 or P. fluorescens 89B61 (Yan et al, 2002). Similarly, colonization of the roots of wildtype and nahG-expressing tomato plants by the non-pathogenic oomycete P. oligandrum resulted in a decrease in Ralstonia solanacearum-inflicted disease symptoms, whereas the ISR response was blocked in mutant jai1 (jasmonic acid insensitive 1) plants (Hase et al, 2008). In addition, using nahG-expressing rice, an ET-insensitive OsEIN2 antisense rice line, and the JA-deficient rice mutant hebiba, De Vleesschauwer et al (2008) demonstrated that the ability of P. fluorescens WCS374r to trigger ISR against the rice leaf blast pathogen Magnaporthe oryzae is regulated by an SA-independent but JA/ET-modulated signaling pathway.…”
Section: Ja-and Et-dependent Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in tomato the JA-insensitive mutant def1 (defenseless 1) and the ET-insensitive mutant Nr (Never ripe) were not capable of mounting ISR against the oomycete pathogen Phytophthora infestans upon colonization of the roots by the PGPR Bacillus pumilus SE34 or P. fluorescens 89B61 (Yan et al, 2002). Similarly, colonization of the roots of wildtype and nahG-expressing tomato plants by the non-pathogenic oomycete P. oligandrum resulted in a decrease in Ralstonia solanacearum-inflicted disease symptoms, whereas the ISR response was blocked in mutant jai1 (jasmonic acid insensitive 1) plants (Hase et al, 2008). In addition, using nahG-expressing rice, an ET-insensitive OsEIN2 antisense rice line, and the JA-deficient rice mutant hebiba, De Vleesschauwer et al (2008) demonstrated that the ability of P. fluorescens WCS374r to trigger ISR against the rice leaf blast pathogen Magnaporthe oryzae is regulated by an SA-independent but JA/ET-modulated signaling pathway.…”
Section: Ja-and Et-dependent Signalingmentioning
confidence: 99%
“…Moreover, transgenic Arabidopsis NahG plants that are unable to accumulate SA due to ectopic expression of the bacterial salicylate hydroxylase gene nahG, showed a similar level of induced disease resistance upon colonization of the roots by WCS417r as did wildtype plants, indicating that WCS417r-ISR functions independently of SA (Pieterse et al, 1996). Since then, many examples of SA-independent ISR have been demonstrated in Arabidopsis (Ahn et al, 2007;Iavicoli et al, 2003;Ryu et al, 2003;Segarra et al, 2009;Stein et al, 2008;Van Wees et al, 1997) and other plant species, such as tobacco (Press et al, 1997;Zhang et al, 2002), cucumber (Press et al, 1997), tomato (Hase et al, 2008;Tran et al, 2007;Yan et al, 2002), and rice (De Vleesschauwer et al, 2008). Hence, the ability to activate an SA-independent pathway controlling systemic disease resistance seems to be common for beneficial microorganisms and occurs in a broad range of plant species against different types of attackers.…”
Section: Sa-independent Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Le Floch and coworkers suggested that mycoparasitism is not the main mode of action (23). Root colonization by P. oligandrum may induce systemic resistance associated with the synthesis of elicitors protecting the plant from its aggressors (4,17,31,37,56). Several studies have investigated formulations of P. oligandrum oospores applied to soil or seeds, and their production and use, to optimize the efficacy of biocontrol (9,30).…”
mentioning
confidence: 99%
“…The antagonists UFV 252, UFV 592 and UFV 618 effectively reduced the Fusarium wilt severity at the same level of hormone JA. JA and its derivatives have been considered as signaling molecules for inducing systemic resistance, which is effective against pathogens with different lifestyles (Hase et al, 2008). In a study using tomato plants incapable of producing JA (def1), plants inoculated with five of eight pathogens were more susceptible to two bacteria (Pseudomonas syringae and X. campestris), two fungi (Verticillium dahliae and Fol) and an oomycete (Phytophthora infestans) but were not altered in their resistance to Cladosporium fulvum, Oidium neolycopersici and Septoria lycopersici.…”
Section: Resultsmentioning
confidence: 99%